INSIGHTS INTO PROSPECTIVE TEACHERS BELIEFS IN TEYL - Hadiyanti, Kayetana Maria Widi; Yolanda, Martha (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
Teacher belief is valuable to accomplish effective teaching learning processes. Prospective teachers utilize their beliefs to practice their teaching competence. Accordingly, it is essential to explore prospective teachers beliefs as the teachers exhibit the beliefs in their teaching preparations and practices. Alongside, TEYL requires a unique process. To enhance TEYL prospective teachers consciousness of the beliefs they hold, this study attempts to match them with the teaching designs and practices. This survey study involves TEYL prospective teachers in responding to a questionnaire concerning with their beliefs about teaching. Their Lesson Plans and teaching performance videos are correspondingly analyzed to scrutinize how equivalent they are with the beliefs. It is quite thought-provoking to discover that there are inconsistencies between prospective teachers beliefs with the realization in their lesson planning and performances. This affords insights to boost our awareness in building teachers beliefs as to maximize learning teaching outcome.